Accumulated and distributed response–reinforcer arrangements during the treatment of escape‐maintained problem behavior. Issue 4 (3rd August 2021) - Frank‐Crawford, Michelle A.; Borrero, John C.; Newcomb, Eli T.; Doan, Trang; Fisher, Alyssa; Rooker, Griffin W.
Abstract : Contingent positive reinforcement has proven more effective in treating escape‐maintained problem behavior than contingent negative reinforcement, particularly when problem behavior continues to produce escape. However, this research has overwhelmingly used distributed‐reinforcement arrangements, where tasks and reinforcer access are interspersed throughout the work period. An alternative to interspersal involves allowing the individual to accumulate and then receive a larger quantity of reinforcement once work requirements are completed; this is known as an accumulated‐reinforcement arrangement. The current study examined the efficacy of, and preference for positive (food) and negative (break) reinforcement contingencies delivered in accumulated and distributed arrangements in the treatment of escape‐maintained problem behavior. In Experiment 1, accumulated break was preferred for 4 of 5 participants and accumulated food was preferred for 3 of 5. In Experiment 2, accumulated break was similarly effective to distributed break for 3 of 5 participants and accumulated and distributed food were equally effective for 4 participants.